P-455 Laparoscopic robot-assisted autologous transplantation of cryopreserved ovarian tissue: report of an operative technique and reproductive outcomes in a case series. (30th June 2022) - Fastrez, M; Simon, P; Dechene, J; Van Den Abbeel, E; Delbaere, A; Demeestere, I
Abstract: Study question: Is laparoscopic robot-assisted autologous transplantation of ovarian tissue feasible and is the reproductive outcome adequate in comparison with published data? Summary answer: Laparoscopic robot-assisted autologous transplantation of ovarian tissue is feasible and safe. The reproductive outcome in our series is comparable with published data. What is known already: Autologous cryopreserved ovarian tissue transplantation (ACOTT) is recognized as a valid fertility preservation technique among young patients facing iatrogenic premature ovarian failure (IOP). Orthotopic transplantation consists in the reimplantation of ovarian tissue back to the medulla of the ovary or into a specially created peritoneal pouch. It has been described by laparoscopy or mini laparotomy. It is the most efficient technique to restore endocrine function and fertility. Conception and live birth rates have been reported to be respectively 38% and 26%. The robot-assisted laparoscopic approach was recently described in a 7-case series. Study design, size, duration: We prospectively registered all ACOTT procedures performed in our department between November 2004 and January 2022. Participants/materials, setting, methods: We analyzed the data of 29 ACOTT procedures performed among 22 patients. The indication for ovarian cryopreservation, the time to restore and duration of endocrine function (regular menstrual cycles), time to first pregnancy and number of pregnancies/live births have been prospectively collected. The operative technique (laparoscopic/robot), duration of surgical procedure, hospital stay, intra and post-operative complications have been retrospectively extracted from the patients' files. Main results and the role of chance: We included 22 patients: 8 with a malignant hematologic disease, 7 with a breast cancer, 3 with a benign disease, 2 with a pelvic malignancy and 2 with a sarcoma. Their median age at ovarian tissue cryopreservation was 28.5 (11 – 35) years. Their median age at first ACOTT was 36.5 (23 – 42) years. The median time between cryopreservation and ACOTT was 6.75 (2 – 21) years. Seven out of 22 patients had a second ACOTT. Twenty-nine procedures of orthotopic reimplantation were performed. A concomitant heterotopic (sub cutaneous) transplantation was performed among six out of the 29 procedures, at the beginning of our experience. All 29 orthotopic reimplantation were performed laparoscopically, 19 out of them with robot assistance. The median operating time was 102 (43 – 149) minutes and was shorter for laparoscopy (62 minutes) than for robot assisted laparoscopy (106 minutes). We encountered no complication, and the median hospital stay was 1 (1 – 2) day. The median time to restore endocrine function was 4 (1 – 6) months. Eighteen transplanted patients wished to be pregnant among whom 12 (67%) had at least one pregnancy and 8 (44%) had at least one live birth. Limitations, reasons for caution: This is a small sample within a single institution. The patients were referred from many centers for ovarian tissue cryopreservation and secondary ACOTT. They were followed until they became pregnant and then referred to their gynecologist. Finally, three patients who did not wish to conceive were lost of follow-up. Wider implications of the findings: This case series confirms the feasibility and safety of robot assisted ACOTT. The procedure is longer when performed with the robot. The fertility outcome (pregnancy/livebirth rates) is comparable with the published data. The added value of the robot approach needs to be investigated in larger series with long term follow-up. Trial registration number: P2004/122